Theory of Motivation in Business Management: An Elaboration of Western and Islamic Worldviews - Hakim, Usmanul; Nidzom, Muhammad Faqih; Mas'ud, Fuad; Anggara, Fajar Surya Ari; Hidayatullah, Rakhmad Agung (Economica: Jurnal Ekonomi Islam, 2022)
This article examines and compares Western and Islamic perspectives on work motivation. Western theories, such as those by Maslow, McGregor, and Herzberg, emphasize secular factors and do not account for worship as a motivation, whereas Islam views worship as the primary driver for work. This suggests that Islamic work motivation stems from a different worldview compared to Western models. The study, a literature review using content and comparative analysis, adopts a philosophical approach with worldview theory as its framework. It consists of two stages: de-westernization, which reviews Western motivation theories, and integration, comparing these theories with Islamic concepts. The findings reveal that Western theories are rooted in secularism, humanism, materialism, and atheism, while Islamic work motivation is based on a non-secular worldview, with God at its center. These differing worldviews result in distinct motivational frameworks in Islam and the West. This study aims to enhance human capital management, particularly in diverse business organizations with heterogeneous workforces.